Impact of hs-CRP concentration on brain structure alterations and cognitive trajectory in Alzheimer’s disease - Zhang, Ye; Tatewaki, Yasuko; Nakase, Taizen; Liu, Yingxu; Tomita, Naoki; Thyreau, Benjamin; Zheng, Haixia; Muranaka, Michiho; Takano, Yumi; Nagasaka, Tatsuo; Taki, Yasuyuki (Frontiers in Aging Neuroscience, 2023)
Introduction Present study was to investigate hs-CRP concentration, brain structural alterations, and cognitive function in the context of AD [Subjective cognitive decline (SCD), mild cognitive impairment (MCI), and AD]. Methods We retrospectively included 313 patients (Mean age = 76.40 years, 59 SCD, 101 MCI, 153 AD) in a cross-sectional analysis and 91 patients (Mean age = 75.83 years, 12 SCD, 43 MCI, 36 AD) in a longitudinal analysis. Multivariable linear regression was conducted to investigate the relationship between hs-CRP concentration and brain structural alterations, and cognitive function, respectively. Results Hs-CRP was positively associated with gray matter volume in the left fusiform (β = 0.16, pFDR = 0.023) and the left parahippocampal gyrus (β = 0.16, pFDR = 0.029). Post hoc analysis revealed that these associations were mainly driven by patients with MCI and AD. The interaction of diagnosis and CRP was significantly associated with annual cognitive changes (β = 0.43, p = 0.008). Among these patients with AD, lower baseline CRP was correlated with greater future cognitive decline (r = −0.41, p = 0.013). Conclusion Our study suggests that increased hs-CRP level may exert protective effect on brain structure alterations and future cognitive changes among patients already with cognitive impairment.